Synthesis and Characterization of Al, Ag, Ti, Cu, and B Substituted Hydroxylapatite - Ergun, Celaletdin; Webster, Thomas J.; Gunes, Gurbuz; Bahadir, Abdurrahman; Liu, Huinan; Erden, Ibrahim (JOHN WILEY & SONS, 2012)
B, Ti, Ag, Al and Cu substituted hydroxylapatites were synthesized via precipitation method. Then the samples were air-sintered at 1300 degrees C for 2 hrs and characterized with XRD, SEM, FTIR, and cell adhesion behaviors.
Keywords: hydroxylapatite; doping; biocompatibility; Materials Science; Metallurgy & Metallurgical Engineering; Mineralogy